Partisipasi Politik Organisasi Karang Taruna dalam Pembangunan Infrastruktur Desa - Ananda Agustina; Izomiddin Izomiddin; Reni Apriani (Jurnal Prodi Ilmu Politik, 2023)
ABSTRACT This research is entitled Political Participation of Youth Organizations in Gunung Agung Village, West Merapi District, Lahat Regency in Village. The inactivity of youth organizations, in this case members of youth organizations in terms of village development, can be seen from three things: First, political activity is a threat to various aspects of their lives. Every decision has a cost or risk. Second, political activity is seen as a futile work. Third, the absence of factors to "stimulate oneself to act" or also known as "political incentives". The purpose of this research is to find out why there can be inactivity of political participation by members of the youth organization in village development and to provide solutions for this inactivity. The method used is a qualitative descriptive approach. The data sources of this research are 50 people and the theory used is the theory of political participation proposed by Morris Rossenberg and Rush and Altof. The results of this study discuss the factors that cause the inactivity of youth organizations of youth organizations in carrying out political participation in village development, such as factors of work, economy, and education. the solutions offered are such as seminars that the theme of political education, well as cooperating with the private sector in fulfilling facilities. Keywords: Political participation, Youth Organizations, Village Development.